Short Form-36 e Body Shape Questionnaire em mulheres em préoperatório de abdominoplastia pós-bariátrica - Rodrigues Huijsmans, Juliana Perez [UNIFESP] (2009)
Introduction: The bariatric surgery. is the most effective treatment for the corporal weight reduction and maintenance of this loss of weight what lead to the cure of the comorbidities associated to the morbid obesity in the most of the cases. The morbid obese patients present more incidences of psycho-emotional alterations and lose quality of life due to they are carry an illness that threat their life, compromises its functional capacity and modifies its corporal image. The post-bariatric plastic surgery brings a new perspective, due to its contribution with the functional, aesthetic, psychosocial improvement and quality of life. Objective: To evaluate the quality of life and corporal image of women in preoperative of Abdominoplasty post-bariatric surgery. Methods: 60 women, 30 from the group in preoperative of plastic post-bariatric surgery (Study) and 30 from group in preoperative of bariatric surgery. (Control) from the Clinic of the Federal University of São Paulo had participated on the study. To make the collection of the data was used the questionnaires Short Form-36 (SF-36) and Body Shape generic and specific Questionnaire (BSQ) respectively generic and specific instruments. For statistics analysis, the Test of Mann-Whitney was used and a level of rejection of 0,05. Results: The two groups presented in the SF-36 in eight dominions significant difference with a rejection level of the nullity hypothesis (p) less that 0.001 in seven dominions. In the eighth (Mental Health) this value was not so small being less that 0,011. The Corporal image was evaluated by the BSQ considerate the total addition of the gotten points the two groups had presented significant difference with a level of rejection of the nullity hypothesis (p) less than 0,001. Conclusion: The quality of life in a general form and the corporal image of the former-morbid obese women in preoperative of Abdominoplasty post-bariatric is better than the morbid obese women.